Manajemen Perilaku Ketidakmandirian Sosial-Emosi Pada Anak Usia Dini Di TK Aisyiyah XIV Kedungwuluh Purwokerto (THUFULA, 2018)
This research is a case study research using qualitative approach. This research is aimed to describe the activity of behavioral management of social-emotion non-self-sufficiency in early childhood in kindergarten Aisyiyah XIV Kedungwuluh Purwokerto. The data in this study were collected using interview technique, observation, and documentation. Then analyzed using data analysis technique inductively. Based on the results of the study can be seen that there are four problems of social-emotional self-sufficiency in early childhood. First, the child strikes school. Second, children do not want to follow the learning activities. Third, the child does not want to be left by his mother. Fourth, children do not want to write or do something. The four issues are then addressed by implementing the 5 steps in the practice of behavioral social-emotional self-reliance behavior in early childhood. First, conduct an analysis of social-emotional self-sufficiency behavior problems in early childhood. Second, create action plans to address the problem of social-emotional self-sufficiency behavior in early childhood. Third, coordinate with the guardian in addressing the problem of social-emotional self-sufficiency behavior in early childhood. Fourth, implementing action handling to overcome the problem of social-emotional self-sufficiency behavior in early childhood. Fifth, assess the success in overcoming the problem of social-emotional self-sufficiency behavior in early childhood.